[OA149] Influence of treatment couch in the secondary MU calculation for VMAT prostate treatments. (August 2018) - Ambroa Rey, Eva Maria; Pardos, Roberto Gomez; Giménez, David Navarro; Quiroga, Julia García-Miguel; Ramirez, Antoni; Truyols, Montserrat Colomer
Abstract : Purpose: Monitor unit (MU) verification of the treatment planning system (TPS) using an independent procedure is a very important component of volumetric modulated arc therapy (VMAT) quality assurance (QA) program. The study was aimed to compare accuracy of monitor unit verification with and without treatment couch, for VMAT prostate treatments. Methods: The accuracy of dose computation by Monaco TPS (v5.10) is checked by independent secondary check software (PTW-Diamond version 6.0). Diamond performs calculation based on modified Clarkson method, which integrates the primary and the scatter components of the radiation dose to a point from all individual and segmental subfields. Dicom files exported from Monaco include RTplan, dose, patient contour and treatment couch structures. Diamond compares results against the TPS. Also, the couch used was Elekta iBEAM evo Couchtop modeled with a density of 0.1 g/cm3 for inner part of foam and 0.5g/cm3 for the carbon fiber shell. A total of 60 patients treated with a single arc of 6MV were included in this study. For every patient MU verification was performed with and without the treatment couch. Results: From 60 patients, the average of MU difference was 0.04% taken into account the treatment couch and 1.23% without the couch, being the maximum found deviation of 3.41% and 4.65% respectively. These differences were statistically significant (p value: 0.00011). The introduction of the treatment couch improves the Diamond results in approximately 68% of the cases. Conclusions: We can conclude that including the treatment couch in the Diamond MU calculations results in a better QA outcome than when the table is not included. We can finish up by saying that incorporate the treatment couch is essential to correctly assess the errors in MU calculations.